Exploration of Visiting Decisions Through Amazing Tourism Attractions And Facilities: a Case Study of the Trokon River - Rahmad Aldino, Fikal; Ghaefira Nur Fatimah (Journal of Managiere and Business, 2024)
An in-depth understanding of the elements that influence tourists' decisions to visit is very important in the era of globalization and increasingly tight competition in the tourism business. This research aims to find out the reasons behind people's decisions to visit the Trokon River, a preferred natural location with attractive facilities and quality views. The aim of this research using case study techniques is to understand the complex interaction between the natural attractions of the Trokon River and the facilities provided, as well as how these two variables influence visitors' decisions to choose this area. Observations and questionnaires are part of the process. The main conclusion of this research shows that the unique attraction of the Trokon River with its beautiful contemporary infrastructure facilities significantly influences visitors' decision to visit. The results of this research provide comprehensive information to tourism destination managers about how to improve tourist facilities and attractions by considering important elements that influence tourists' decisions to come. Pemahaman mendalam mengenai unsur-unsur yang mempengaruhi keputusan wisatawan untuk berkunjung sangat penting di era globalisasi dan persaingan bisnis pariwisata yang semakin ketat. Penelitian ini bertujuan untuk mengetahui alasan yang melatarbelakangi keputusan masyarakat mengunjungi Sungai Trokon, lokasi alam yang disukai dengan fasilitas menarik dan pemandangan berkualitas. Tujuan dari penelitian ini dengan menggunakan teknik studi kasus adalah untuk memahami interaksi kompleks antara objek wisata alam Sungai Trokon dengan fasilitas yang disediakan, serta bagaimana kedua variabel tersebut mempengaruhi keputusan pengunjung untuk memilih kawasan tersebut. Observasi dan kuesioner adalah bagian dari proses. Kesimpulan utama penelitian ini menunjukkan bahwa keunikan daya tarik Sungai Trokon dengan fasilitas infrastruktur kontemporer yang indah berpengaruh signifikan terhadap keputusan pengunjung untuk berkunjung. Hasil penelitian ini memberikan informasi yang komprehensif kepada pengelola destinasi pariwisata tentang cara meningkatkan fasilitas dan daya tarik wisata dengan mempertimbangkan unsur-unsur penting yang mempengaruhi keputusan wisatawan untuk datang.